Sustainable preparation method of power generation veneer

By using a low eutectic solvent to treat wood, remove lignin and grow zinc oxide, and change the structure of wood cell walls, the problem of insufficient compression and resilience performance of wood in the prior art is solved, and efficient and environmentally friendly preparation of thin wood for power generation is achieved, with good mechanical and piezoelectric properties.

CN119871619APending Publication Date: 2025-04-25DEHUA TB NEW DECORATION MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510026482.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively regulate the micro-nano structure of wood to improve its compression and resilience performance, and the commonly used treatment methods are complex and cumbersome and pollute the environment, which cannot meet the needs of large-scale applications and sustainable development.

Method used

The wood is treated with eutectic solvents, and the lignin and growth zinc oxide in the wood are removed by eutectic solvents of the choline chloride-lactic acid system and zinc chloride-urea system, respectively, to change the structure of the wood cell wall, thereby improving its piezoelectric properties.

Benefits of technology

It has achieved the improvement of the mechanical properties of wood and the stability of voltage output, and has good mechanical properties and excellent piezoelectric properties, and the treatment method is environmentally friendly and efficient, and meets the requirements of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119871619A_ABST
    Figure CN119871619A_ABST
Patent Text Reader

Abstract

The invention discloses a sustainable preparation method of a power generation veneer, which is used for successfully preparing the power generation veneer by using wood such as cork wood as a raw material and treating the raw material by using a deep-eutectic solvent. The method comprises the following steps: firstly, selectively removing wood lignin by using a choline chloride-lactic acid system eutectic solvent to obtain a power generation veneer substrate; in the process, on one hand, the pore structure of the wood cell wall is changed, so that a structural basis is provided for the subsequent continuous piezoelectric effect; on one hand, the solvent has a moistening and swelling effect on cellulose, so that reagent permeation is facilitated; and then zinc oxide grows on the surface of the power generation veneer substrate through zinc chloride and urea system eutectic solvent treatment, the piezoelectric property of the veneer is further improved, and finally the power generation veneer is obtained. According to the method, part of lignin in the wood is efficiently removed under the relatively mild reaction condition, the problems that the lignin removal efficiency is low and the environment is not protected are effectively solved, and meanwhile reliable technical support is provided for developing the veneer wood which is environmentally friendly, good in mechanical property and excellent in piezoelectric property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of wood functional modification, and in particular relates to a sustainable preparation method of power-generating veneer. Background Art

[0002] With the development of Internet of Things technology and artificial intelligence, smart homes are increasingly entering people's horizons, among which smart responsive home wood products have received widespread attention. As the most widely used home material, wood is expected to be used as a micro generator in the field of smart homes due to its good processability, environmental friendliness and its own piezoelectric effect. This has positive significance for the high-value utilization of wood and the response to the national energy conservation and emission reduction policy. Piezoelectric nanogenerators convert mechanical energy into electrical energy through the piezoelectric effect of the material itself. If they can be applied to smart home products to achieve self-powered, it will break the traditional power supply method and provide a new idea for the development of smart homes. For this reason, piezoelectric nanogenerators based on wood came into being. Their structure is to connect wires at both ends of the wood to form a loop, and to generate a potential difference by applying mechanical force to output current.

[0003] However, due to the low piezoelectric modulus and limited deformation capacity of wood itself, its charge output efficiency as a piezoelectric nanogenerator is greatly limited. Considering that the key to the piezoelectric effect of wood is the voltage generated by elastic deformation, constructing wood with a highly compressible rebound structure has become a focus of researchers at home and abroad. Related studies have obtained a multilayer cellulose network through delignification treatment, making the modified wood have good compressible resilience, thereby improving the piezoelectric effect of wood; in addition, some researchers have treated the cell walls of wood through fungal corrosion to form an arched layered structure, which is also conducive to the high compression and rebound of wood. Therefore, the micro-nano structure of the wood itself is crucial to its compression and rebound properties.

[0004] In recent years, there have been numerous reports and studies on various chemical methods used to change the chemical composition and pore structure of wood to improve its compression and resilience properties, such as acid-base treatment, sodium chlorite treatment, sodium hydroxide and sodium sulfite treatment, hydrogen peroxide treatment, etc. However, these treatment methods are complicated and pollute the environment, and cannot meet the large-scale application and sustainable development of highly compressive and resilient wood for the time being. Therefore, it is necessary to seek a green and sustainable treatment method to effectively regulate the micro-nano structure of wood to improve its compression and resilience properties.

[0005] As a new type of chemical substance with the advantages of low cost, good ecological properties and low toxicity, low eutectic solvents are composed of hydrogen bond donors and hydrogen bond acceptors. They contain large and asymmetric ions, which leads to low lattice energy and thus low melting point. Due to the ability to provide and accept protons, low eutectic solvents can form abundant hydrogen bonds, thus having good solvation properties for polar and non-polar compounds. When using low eutectic solvents to remove lignin from wood, no environmentally harmful gases will be produced during the reaction, and the low eutectic solvents after the reaction can be recycled and reused, which is in line with the idea of ​​green energy conservation; in addition, low eutectic solvents have better selective removal ability for wood lignin and better protection for the wood's own structure, which can effectively retain wood cellulose and its hierarchical structure to improve the piezoelectric properties of wood. Summary of the invention

[0006] In view of the above-mentioned technical deficiencies, the purpose of the present invention is to provide a sustainable preparation method for power-generating veneer, by treating the veneer with a low eutectic solvent, removing the lignin in the wood, changing the cell wall structure of the wood, thereby preparing a power-generating veneer substrate, and by testing the mechanical properties and piezoelectric properties of the veneer substrate and the original wood, a group of veneers with higher mechanical properties and more stable voltage output can be obtained; and the veneer substrate is further treated with a zinc chloride-urea solution, and zinc oxide is in situ grown on the surface of the veneer substrate to improve the piezoelectric properties of the veneer substrate, and finally a power-generating veneer with good mechanical properties and excellent piezoelectric properties is obtained.

[0007] In order to solve the above technical problems, the present invention provides the following technical solution: a sustainable preparation method for power generation veneer, the steps are as follows: Step 1: preparation of a low eutectic solvent: including preparation of a choline chloride-lactic acid system low eutectic solvent and a zinc chloride-urea system low eutectic solvent; Step 2: Preparation of power generation veneer substrate: saw three different thicknesses of original balsa wood into balsa wood chips of a certain size, completely immerse the three thicknesses of balsa wood chips in a low eutectic solvent of choline chloride-lactic acid system, heat at 90°C for 3 hours until the chips completely change color, take out the chips, first wash the low eutectic solvent remaining on the chips with deionized water, then rinse the chips with a mixture of anhydrous ethanol and deionized water until there is no solvent remaining on the chips, and dry them at 60°C for 12 hours to obtain a power generation veneer substrate; Step 3: Preparation of high-performance power-generating veneer: immerse the power-generating veneer base treated and dried in the previous step in a low eutectic solvent of zinc chloride-urea system, and react at 110°C for 3 hours. After the reaction is completed, rinse the treated wood chips with a mixed solution of anhydrous ethanol and deionized water. After washing, place the wood chips in an electric heated forced air drying oven and dry them at 60°C for 12 hours to obtain high-performance power-generating veneer.

[0008] Preferably, the step of preparing the choline chloride-lactic acid system low eutectic solvent in step one is as follows: according to the molar ratio of choline chloride to lactic acid being 1:10, 26.84 g of choline chloride is added to 173.16 g of lactic acid, magnetically stirred for 10 min to mix evenly, and then stirred at 80 ° C for 2 h until the solution is transparent.

[0009] Preferably, in step 1, after there is no residual solid precipitation in the beaker and the solution is transparent, heating and stirring are stopped to obtain 200 g of a choline chloride-lactic acid system low eutectic solvent.

[0010] Preferably, the step of preparing the zinc chloride-urea system low eutectic solvent in step 1 is as follows: according to the molar ratio of zinc chloride to urea of ​​1:10, 43.07g of zinc chloride is added to 56.93g of urea, magnetically stirred for 10min to mix evenly, and then stirred at 110°C for 2h until the solution is transparent.

[0011] Preferably, the three thicknesses of balsa wood chips in step 2 are 1 mm, 3 mm and 5 mm respectively, and have a size of 4 cm in length and 2 cm in width.

[0012] Preferably, the high-performance power generation veneer wood species obtained in step three include balsa wood, basswood or other broadleaf wood species.

[0013] Preferably, in step three, the number of times the treated wood chips are rinsed with the mixed solution of anhydrous ethanol and deionized water is 4 times.

[0014] Compared with the existing piezoelectric wood preparation method, the advantages of the present invention are: (1) the preparation method is energy-saving, environmentally friendly and efficient, and the low eutectic solvent can be reused, realizing green and efficient development, which is in line with the national energy conservation and emission reduction theme; (2) part of the wood lignin is retained, which not only gives the modified wood certain mechanical properties, but also effectively enhances its piezoelectric properties; (3) the porous and layered structure of wood is conducive to the in-situ growth of high-voltage electrical materials, ensuring the effective load of high-voltage electrical materials in the wood substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The mechanical properties of a power generation veneer substrate prepared in Example 1 of the present invention; Figure 2 The voltage output performance of a high-performance power-generating veneer prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0016] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0017] (1) Preparation of choline chloride-lactic acid system deep eutectic solvent (DES): (1) Prepare 200 g of choline chloride-lactic acid system DES solvent, with the molar ratio of choline chloride to lactic acid being 1:10. Take 26.84 g of choline chloride white granules and add them to 173.16 g of lactic acid solution. Set the heating temperature to 80 °C and stir for 2 h until the solution becomes transparent.

[0018] (2) Preparation of power generation veneer substrate: First, the original balsa wood with a thickness of 1 mm was sawn into wood chips with a size of 4 cm*2 cm (length*width). The wood chips were completely immersed in the low eutectic solvent at a ratio of 10 ml of the low eutectic solvent prepared above to one wood chip. The wood chips were heated to 110°C and stirred for 3 hours. After the reaction was completed, the wood chips were taken out and the residual solvent on the wood chips was washed with deionized water. The wood chips were then rinsed with a mixture of anhydrous ethanol and deionized water until there was no low eutectic solvent left on the wood chips. The wood chips were placed in an electric hot air drying oven and dried at 60°C for 12 hours to finally obtain a power generation veneer substrate. Example

[0019] (1) Preparation of zinc chloride-urea solvent: 100 g of zinc chloride-urea solvent was prepared, with the molar ratio of zinc chloride to urea being 1:3. 43.07 g of zinc chloride was added to 56.93 g of urea. The mixture was then stirred at 110° C. for 4 h until the mixed solution became transparent, and then heating and stirring were stopped.

[0020] (2) Preparation of high-performance power-generating veneer: The dried 1mm power-generating veneer substrate was completely immersed in the solution for heating treatment at a ratio of 10ml zinc chloride-urea solution to one wood chip, and the reaction temperature and time were set to 110℃ and 4h respectively. After the treatment, the wood chips were taken out and rinsed with a mixed solution of anhydrous ethanol and deionized water. After washing, the wood chips were placed in an electric hot air drying oven at 60℃ and dried overnight for use. In addition, the voltage output performance of the original wood sample with a length*width*thickness of 2cm*2cm*1mm, the power-generating veneer substrate, and the high-performance power-generating veneer is shown in Table 1, showing excellent voltage output performance. The present invention uses balsa wood and other wood as raw materials, and successfully prepares power-generating veneer by treating with a low eutectic solvent. The wood lignin is selectively removed using a choline chloride-lactic acid system low eutectic solvent to obtain a power-generating veneer substrate. In this process, on the one hand, the pore structure of the wood cell wall changes, thereby providing a structural basis for the subsequent piezoelectric effect; on the other hand, the solvent has a swelling effect on cellulose, which is more conducive to the penetration of reagents. Subsequently, zinc oxide is grown on the surface of the power-generating veneer substrate by treating with a zinc chloride and urea system low eutectic solvent, further improving the piezoelectric properties of the wood slices, and finally obtaining power-generating veneer. The present invention efficiently removes part of the lignin in the wood under relatively mild reaction conditions, effectively solving the problems of low delignification efficiency and environmental pollution. At the same time, the present invention provides reliable technical support for the development of veneer wood that is both green and environmentally friendly, has good mechanical properties, and has excellent piezoelectric properties.

[0021] Although specific embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit thereof, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A sustainable preparation method for power generation veneer, characterized in that: Here are the steps: Step 1: preparation of a low eutectic solvent: including preparation of a choline chloride-lactic acid system low eutectic solvent and a zinc chloride-urea system low eutectic solvent; Step 2: Preparation of power generation veneer substrate: saw three different thicknesses of original balsa wood into balsa wood chips of a certain size, completely immerse the three thicknesses of balsa wood chips in a choline chloride-lactic acid system low eutectic solvent, heat at 90°C for 3h, take out the wood chips, first wash the low eutectic solvent remaining on the wood chips with deionized water, then rinse the wood chips with a mixture of anhydrous ethanol and deionized water until there is no solvent remaining on the wood chips, and dry them at 60°C for 12h to obtain a power generation veneer substrate; Step 3: Preparation of high-performance power-generating veneer: immerse the power-generating veneer base treated and dried in the previous step in a low eutectic solvent of zinc chloride-urea system, and react at 110°C for 3 hours. After the reaction is completed, rinse the treated wood chips with a mixed solution of anhydrous ethanol and deionized water. After washing, place the wood chips in an electric heated forced air drying oven and dry them at 60°C for 12 hours to obtain high-performance power-generating veneer.

2. The sustainable preparation method of power generation veneer according to claim 1, characterized in that: The steps for preparing the choline chloride-lactic acid system low eutectic solvent in step 1 are as follows: according to the molar ratio of choline chloride to lactic acid being 1:10, 26.84 g of choline chloride is added to 173.16 g of lactic acid, magnetic stirring is performed for 10 min to mix the mixture evenly, and then stirring is performed at 80° C. for 2 h until the solution becomes transparent.

3. The sustainable preparation method of power generation veneer according to claim 2, characterized in that: In the step 1, after there is no residual solid precipitation in the beaker and the solution is transparent, heating and stirring are stopped to obtain 200 g of a choline chloride-lactic acid system low eutectic solvent.

4. The sustainable preparation method of power generation veneer according to claim 1, characterized in that: The steps for preparing the zinc chloride-urea system low eutectic solvent in the step 1 are as follows: according to the molar ratio of zinc chloride to urea of ​​1:10, 43.07g of zinc chloride is added to 56.93g of urea, magnetic stirring is performed for 10min to mix the mixture evenly, and then stirring is performed at 110°C for 2h until the solution becomes transparent.

5. The sustainable preparation method of power generation veneer according to claim 1 is characterized by: The thicknesses of the three types of balsa wood chips in step 2 are 1 mm, 3 mm, and 5 mm, respectively, and the sizes are 4 cm in length and 2 cm in width.

6. The sustainable preparation method of power generation veneer according to claim 1, characterized in that: The high-performance power generation veneer wood obtained in step three includes balsa wood, basswood or other broadleaf wood species.

7. The sustainable preparation method of power generation veneer according to claim 1, characterized in that: In the step 3, the treated wood chips are rinsed 4 times with a mixed solution of anhydrous ethanol and deionized water.